A Review of the Immunological Mechanisms Following Mucosal Vaccination of Finfish - Munang’andu, Hetron Mweemba; Mutoloki, Stephen; Evensen, Øystein (Frontiers in Immunology, 2015)
Mucosal organs are principle portals of entry for microbial invasion and as such developing protective vaccines against these pathogens can serve as a first line of defense against infections. In general, all mucosal organs in finfish are covered by a layer of mucus whose main function is not only to prevent pathogen attachment by being continuously secreted and sloughing-off but it serves as a vehicle for antimicrobial compounds, complement and immunoglobulins that degrade, opsonize and neutralize invading pathogens on mucosal surfaces. In addition, all mucosal organs in finfish possess antigen presentation cells (APCs) that activate cells of the adaptive immune system to generate long lasting protective immune responses. The functional activities of APCs are orchestrated by a vast array of proinflammatory cytokines and chemokines found in all mucosal organs. The adaptive immune system in mucosal organs is made of humoral immune responses able to neutralize invading pathogens as well as cellular mediated immune responses whose kinetics are comparable to those induced by parenteral vaccines. In general, finfish mucosal immune system has the capacity to serve as the first line defense mechanism against microbial invasion as well as being responsive to vaccination.